Hereditary angioedema in children and adolescents – A consensus update on therapeutic strategies for German‐speaking countries. Issue 8 (16th July 2020) - Wahn, Volker; Aberer, Werner; Aygören‐Pürsün, Emel; Bork, Konrad; Eberl, Wolfgang; Faßhauer, Maria; Krüger, Renate; Magerl, Markus; Martinez‐Saguer, Inmaculada; Späth, Peter; Staubach‐Renz, Petra; Weber‐Chrysochoou, Christina
Abstract: Background/Methods: At a consensus meeting in August 2018, pediatricians and dermatologists from German‐speaking countries discussed the therapeutic strategy for the treatment of pediatric patients with type I and II hereditary angioedema due to C1 inhibitor deficiency (HAE‐C1‐INH) for Germany, Austria, and Switzerland, taking into account the current marketing approval status. HAE‐C1‐INH is a rare disease that usually presents during childhood or adolescence with intermittent episodes of potentially life‐threatening angioedema. Diagnosis as early as possible and an optimal management of the disease are important to avoid ineffective therapies and to properly treat swelling attacks. This article provides recommendations for developing appropriate treatment strategies in the management of HAE‐C1‐INH in pediatric patients in German‐speaking countries. An overview of available drugs in this age‐group is provided, together with their approval status, and study results obtained in adults and pediatric patients. Results/Conclusion: Currently, plasma‐derived C1 inhibitor concentrates have the broadest approval status and are considered the best available option for on‐demand treatment of HAE‐C1‐INH attacks and for short‐ and long‐term prophylaxis across all pediatric age‐groups in German‐speaking countries. For on‐demand treatment of children aged 2 years and older, recombinant C1‐INH and bradykinin‐receptor antagonist icatibant are alternatives. For long‐term prophylaxis in adolescents, the parenteral kallikrein inhibitor lanadelumab has recently been approved and can be recommended due to proven efficacy and safety.